Multilevel Participation and Dynamics of Community Project Initiative in Nigeria: A Study of Fourth-Tier Development and Governance in Anambra State, 2016-2021. - AMALI, Anthony-Mary Chukwudozie; BIEREENU-NNABUGWU, Makodi (Socialscientia: Journal of Social Sciences and Humanities, 2024)
This paper explores “Multilevel Participation and Dynamics of Community Project Initiative in Nigeria: A Study in Fourth-Tier Development and Governance, in Anambra State 2016-2021.” Community development, devolution of power and decentralization of decision-making and governance have become crucial worldwide due to the rise in government activities, population growth, and development needs. No doubt in Nigeria, the three tiered system of government has become inadequate due to population and increased government activities. The top-down development model preferred by the government in Nigeria have rather aided disjointed and total absence of development in rural communities. This gives rise for the need to study bottom-up development model that suit the African history of small autonomous nationalities to galvanized development. This paper, therefore, explore the roles(s} of various government, and nongovernment actors in the development governance of projects, and to what extant their involvement has impacted the success of local initiatives in Anambra state. The study is primarily a qualitative one and adopts explanatory research design. Data was generated from secondary sources. The secondary data was complemented with key informant interview (KII) while the secondary data were sourced from books, government publications and other relevant document. The bulk of data generated was analyzed through textual method of data analysis. Using the Public Choice theory, the study argues that the Project though a bottom-top developmental model could not achieve much community development due to combination of factors. These includes but not limited to lack of law to recognize communities as a tier or arm of government that should spelt out functions of the PGs and traditional leaders of the communities. The result further shows that the people were not substantially involved in the decision-making at the grass-root and that there were pervasive corruption and looting of common wealth by staketakers (stakeholders) of the communities and party members among others.